Application of Digital Menu Design and Student's Cognitive Level in Food Plating Technique - Md Sahak, Adibah Aishah; Abdul Wafi Abdul Rahman; Nurul Falah Hashim (Online Journal for TVET Practitioners, 2022)
The cognitive level of students in practical subjects is influenced by various external and internal factors. Cognitive is one of the important elements for students towards the achievement of better skills. The need to strengthen the cognitive level among TVET students has become a priority in the field of education. Effective pedagogical approach should focus on increasing culinary students’ understanding of plating technique. Therefore, the objective of this study is to identify culinary student’s experience using digital platform for plating technique activities, to identify cognitive level of students to understand plating techniques through digital menu design and identify the suitability of culinary students to learn plating techniques digitally. The 63 students from the culinary program who enrolled in practical course. The survey design applied to conduct the research and set of questionnaires as instrument for data collection. The dimension measures are student’s experience, student’s cognitive level and suitability of learning with digital platform. The results of this study show that teaching using digital design for practical classes is an effective teaching that is expected to improve students' cognitive levels and indirectly improve student achievement. Hence, the digital menu design concept perhaps could be applied in other learning content and alternative teaching method in culinary program.